Effect of different modalities of transcranial magnetic stimulation on Parkinson’s patients cognitive impairment and long-term effectiveness: a systematic review and network meta-analysis - Yang, Yulin; Yan, Zhenyang; Chang, Wanpeng; Ding, Jiangtao; Xu, Hongli (Frontiers in Neuroscience, 2024)
This study used network Meta-analysis to compare the effects of different transcranial magnetic stimulation (TMS) modalities on the effectiveness and long-term validity of improving cognitive function in Parkinson's patients. Methods: Computer searches of the Cochrane Library, PubMed, Web of Science, Embass, CNKI and Wanfang Data were conducted to collect randomized controlled clinical studies on TMS to improve cognitive function in Parkinson's patients published from the time of library construction to December 2023. Results: A total of 22 studies and 1473 patients were included, comprising 5 interventions: high frequency repetitive transcranial magnetic stimulation (HF-rTMS), low frequency repetitive transcranial magnetic stimulation (LF-rTMS), intermittent theta burst stimulation (iTBS), sham stimulation and conventional rehabilitation therapy (CRT). Network Meta-analysis showed that the ranking results of different TMS intervention modalities in terms of MoCA scores were: HF-rTMS > LF-rTMS > iTBS > sham > CRT, the ranking results of different TMS intervention modalities in terms of MMSE scores were: HF-rTMS > LF-rTMS > sham > CRT. The effect of TMS on improving Parkinsonian cognitive function lasted for one month compared to the no-stimulation group. Conclusions: TMS has some long-term sustained effects on improving cognitive function in Parkinson's patients. HF-rTMS is more effective in improving cognitive function in Parkinson's patients.